Sudden Cardiac Death Survival Prediction from Restitution Dispersion Analysis - Ramírez, Julia; Mincholé, Ana; Bolea, Juan; Laguna, Pablo; Pueyo, Esther (Jornada de Jóvenes Investigadores del I3A, 2014)
Increase in the dispersion of action potential duration restitution (APDR) has been associated with sudden cardiac death (SCD). A marker, Δα, was proposed to quantify APDR dispersion from the electrocardiogram (ECG). 609 ECG recordings were analysed. The marker Δα stratified patients according to their risk of suffering from SCD.